Guanidinium Ylide Mediated Aziridination from Arylaldehydes: Scope and Limitations in the Formation of Unactivated 3-Arylaziridine-2-carboxylates - Oda, Yukiko; Hada, Kihito; Miyata, Marie; Takahata, Chisato; Hayashi, Yukiko; Takahashi, Masato; Yajima, Naoki; Fujinami, Makiko; Ishikawa, Tsutomu (Synthesis, 2014)
The scope and limitations of guanidinium ylide mediated aziridinations from arylaldehydes yielding unactivated 3-arylaziridine-2-carboxylates, applicable to asymmetric synthesis, are discussed.
Keywords: aldehydes; asymmetric synthesis; chiral auxiliaries; esters; ylides